The Difference in Severity of Temporomandibular Joint Disorders Before and After Jaw Exercises - Chairunnisa, Ricca; Nasution, Hubban; Maheswari, Uma (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The temporomandibular joint is part of the stomatognathic system, where interference with one component of the stomatognathic system will interfere with other components causing an imbalance of function. One such disorder is temporomandibular. Temporomandibular disorders have signs, symptoms, and severity that can be eliminated through jaw exercises. This study had the goal of evaluating and comparing the severity of TMD symptoms between students before and after engaging in jaw exercises In this purposive sampling study, researchers used questionnaires based on the Helchymo Anamnestic Index. 30 respondents who complained of temporomandibular disorder were asked to fill out a questionnaire through a Google form. Patients with TMD were inferred based on the total score of all questions with paired T-test statistical results. The results showed that there was a difference in severity before and after jaw exercise in 24 (80%) patients. There was a difference in the severity of temporomandibular joint disorders before and after jaw exercise by patients with p-value = 0.0001 (p <0.005).